Laser cladding WC particle reinforced nickel-based alloy gradient composite coating on surface of non-magnetic steel

By using magnetless steel surface laser cladding WC particles to enhance the nickel-based alloy gradient composite coating under harsh working conditions such as oil and gas mining, the problem of insufficient hardness and wear resistance of the traditional coating is solved, and higher bonding strength and resistance are achieved, and the service life of the material is extended.

CN119876938APending Publication Date: 2025-04-25SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510090899.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional laser clad nickel-based alloy coatings show insufficient hardness and wear resistance under severe working conditions such as oil and gas mining. The combination strength is low, and it is prone to peeling and corrosion failure, and thermal expansion mismatch causes stress concentration problems.

Method used

The nickel-based alloy gradient composite coating is enhanced by laser cladding of WC particles on the surface of magnet-free steel. Through the gradient design of Inconel 625 alloy powder and tungsten carbide WC particles, a three-layer structure is formed, with each layer thickness of 0.9~1.1mm, the first gradient sublayer is 100% Inconel625, the second gradient sublayer is 85% Inconel625-15% WC, and the third gradient sublayer is 70% Inconel625-30% WC.

Benefits of technology

It significantly improves the bonding strength, microhardness, wear, corrosion and thermal cycling resistance of the coating, reduces thermal expansion mismatch stress and interface pressure, extends the service life of the material, and reduces maintenance costs and operation risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876938A_ABST
    Figure CN119876938A_ABST
Patent Text Reader

Abstract

The invention discloses a laser cladding WC particle reinforced nickel base alloy gradient composite coating on the surface of non-magnetic steel, and a preparation method of the composite coating aims at the problem that the performance of the non-magnetic steel in a severe service environment is insufficient, and comprises the following steps: firstly, carrying out mechanical grinding, abrasive paper polishing and ethanol cleaning pretreatment on a TWZ-2 non-magnetic steel substrate; inconel 625 and WC spherical powder with a specific particle size are adopted for cladding, and a bottom layer (Inconel 625-0% WC), a middle layer (Inconel 625-15% WC) and a top layer (Inconel 625-30% WC) are subjected to a structure design gradient process; the laser power is 2400W, 2600W and 2900W in sequence; the scanning speed is 750 mm / min, the scanning speed is 650 mm / min, and the scanning speed is 780 mm / min; the powder feeding speed is 21.6 g / min, 23.8 g / min and 28.4 g / min; and the lap joint rate is 45%. The substrate is preheated at 250 DEG C before cladding, is subjected to heat preservation for half an hour, and then is slowly cooled to room temperature; the gradient composite coating prepared through the technology is compact in structure, free of defects and good in combination with a matrix, WC refines grains, the hardness, strength, toughness and abrasion resistance are improved through multiple strengthening mechanisms, the hardness of the coating is distributed in a gradient mode, and the requirement for the high-performance surface of non-magnetic steel in multiple fields is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser additive manufacturing, and in particular to a WC particle reinforced nickel-based alloy gradient composite coating laser clad on a non-magnetic steel surface and a preparation method thereof, wherein the nickel-based alloy is Inconel 625 alloy powder. Background Art

[0002] In the field of material surface modification, laser cladding technology is one of the important means to improve the surface performance of materials. Nickel-based alloys have become commonly used laser cladding materials due to their excellent anti-oxidation, corrosion resistance, penetration and high-temperature self-lubrication properties. However, under harsh working conditions such as oil and gas extraction, traditional laser cladding nickel-based alloy coatings have gradually exposed many defects.

[0003] In terms of hardness and wear resistance, its hardness and wear resistance are limited, and it is difficult to meet the use requirements of tools such as non-magnetic drill collars in complex stress and frequent wear environments, causing the drill collars to easily fail due to wear, seriously affecting the efficiency and safety of mining operations.

[0004] From the perspective of bonding performance, the significant differences in thermal physical and mechanical properties between the base material and the nickel-based coating result in a low bonding strength between the two. The coating is prone to peeling during service and cannot provide long-term and stable protection for the base.

[0005] In terms of stress, the thermal expansion mismatch between the coating and the substrate causes serious stress concentration problems, which in turn generates a large number of cracks and holes, which not only weakens the performance of the coating itself, but also provides an intrusion channel for the corrosive medium, accelerates the corrosion failure process of the material, reduces the overall service life of the material, and increases maintenance costs and operational risks. Therefore, it is urgent to develop a new coating technology that can effectively overcome the above defects. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a WC particle reinforced nickel-based alloy gradient composite coating laser clad on the surface of non-magnetic steel and a preparation method thereof, aiming to solve the problems of low strength and hardness of the alloy materials manufactured using the coating of the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: In the first aspect, a WC particle reinforced nickel-based alloy gradient composite coating is laser clad on the surface of non-magnetic steel. The raw materials of the composite coating are Inconel 625 alloy powder and tungsten carbide WC particles. The gradient composite coating is divided into three layers, and the thickness of each layer is 0.9~1.1mm.

[0008] Furthermore, the mass percentages of the Inconel 625 alloy powder and tungsten carbide WC particles in different gradients are: first gradient sublayer: 100% Inconel 625 - 0% tungsten carbide WC, second gradient sublayer: 85% Inconel 625 -15% tungsten carbide WC, third gradient sublayer: 70% Inconel 625 -30% tungsten carbide WC, wherein the particle size of the Inconel 625 alloy powder is 53-150 μm; the particle size of the tungsten carbide WC particles is 30-80 μm.

[0009] In the second aspect, a method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface comprises: Step 1, ball-milling and mixing Inconel 625 alloy powder and WC particles to obtain mixed powder; Step 2: Put the mixed powder into a beaker and place it in a drying oven for drying to obtain dry powder; Step 3, pre-treating the substrate surface; Step 4: The dry powder is clad onto the treated substrate through a synchronous powder feeding laser cladding device to obtain a WC particle reinforced Inconel 625 composite coating.

[0010] Furthermore, in step 1, the ball mill stirs the mixed powder at a rotation speed of 200-500 rpm for 12-24 hours, and the mass percentage of the ball-milled mixed ceramic balls and the alloy powder is 1:1.

[0011] Furthermore, in step 1, the mass percentage of the ball-milled mixture of the Inconel 625 alloy powder and the WC particles is divided into three gradients: the first gradient sublayer: 100% Inconel 625 - 0% WC, the second gradient sublayer (middle layer): 85% Inconel 625 - 15% WC, the third gradient sublayer (top layer): 70% Inconel 625 - 30% WC, wherein the particle size of the Inconel 625 alloy powder is 53-150 μm; the particle size of the WC particles is 30-80 μm.

[0012] Furthermore, in step 2, the operating temperature of the drying oven is 120-150° C., and the time is 8-12 hours.

[0013] Furthermore, in step 3, the substrate is pretreated by removing the oxide layer on the surface of the substrate by mechanical grinding, then polishing it flat with sandpaper, and then cleaning it with an ethanol solution to remove surface oil stains.

[0014] Furthermore, in step 4, the laser cladding process parameters are different according to the levels: the laser powers are 2400W, 2600W, and 2900W respectively; the scanning rates are 750mm / min, 650mm / min, and 780mm / min respectively; the powder feeding rates are 21.6g / min, 23.8g / min, and 28.4g / min; and the overlap rates are all 45%.

[0015] Further, in step 4, the gradient composite coating is divided into three layers, each layer having a thickness of 0.9 to 1.1 mm. The technical solution adopted by the present invention has the following beneficial effects: 1. Compared with ordinary and single-component coatings, the gradient coating of the present invention using WC particle dispersion strengthening Inconel 625 alloy coating improves bonding strength, microhardness, wear, corrosion and thermal cycle resistance, reduces thermal expansion mismatch stress and interface pressure, crack driving force, delamination, warping and pores.

[0016] 2. WC particles have high hardness (Vickers hardness can reach 2400-2600HV), playing a key strengthening role in the coating. As the WC content in the gradient coating gradually increases from 0% wt to 30% wt, the hard phase in the coating increases, and the hardness and strength of the coating are significantly improved through the synergistic effect of multiple mechanisms such as solid solution strengthening, precipitation strengthening, fine grain strengthening and dispersion strengthening. For example, the average microhardness of the third gradient sublayer reaches 1.73 times that of the substrate, and is higher than that of the Inconel625 + 30% WC single composite coating, which effectively enhances the material surface's ability to resist deformation and wear.

[0017] 3. The gradient structure design is adopted to achieve a gradual transition from the substrate to the coating surface composition. This transition avoids the sudden change in strength and toughness between the coating and the substrate, minimizes the thermal expansion mismatch and interface stress factor between the coatings, effectively reduces the stress concentration between the coating interfaces, reduces the tendency of crack initiation, obtains a good interface bonding effect, improves the bonding strength between the coating and the substrate, and enhances the overall stability and reliability of the coating. The reasonable setting of the WC content in different gradient sublayers makes the coating gradually change its performance from the inside to the outside, forming a structure with a hard surface and a tough inside. The high hardness and wear resistance of the surface can effectively resist external wear and corrosion, and the higher plasticity and toughness of the core can provide good support for the coating, prevent the overall brittle fracture of the coating, and improve the adaptability and service life of the coating under complex working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Attached Figure 1 They are the SEM overall morphology of the gradient composite coating, the enlarged view of the bonding area between the bottom layer and the substrate, and the enlarged view of the bonding area between the bottom layer and the middle layer; Attached Figure 2 This is the metallographic microscopic morphology of the gradient coating; Attached Figure 3 This is a scanning electron microscopy image of the gradient coating; Attached Figure 4 It is the element content diagram of the test point of the gradient cladding layer; Attached Figure 5 XRD patterns of gradient coating and single coating; Attached Figure 6 It is the EDS line scan image around the undissolved WC powder particles; Attached Figure 7 is the microhardness distribution diagram of the gradient coating; Attached Figure 8 is the friction coefficient diagram of the gradient cladding layer; Attached Fig. 9 is the wear volume diagram of gradient cladding layer; Attached Fig.10 The wear morphology of substrate and coating; Attached Fig.11 Comparison diagram of three-dimensional morphological parameters of substrate and coatings with different WC contents; Attached Fig.12 The first gradient image of the three-dimensional morphology of the wear scar of the gradient coating; Attached Fig.13 The second gradient image of the three-dimensional morphology of the wear scar of the gradient coating Attached Fig.14 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] The specific implementation of the present application is described in detail with the help of the following examples, but the scope of protection claimed by the present invention is not limited to the following specific implementation examples, and all related equivalent substitutions based on this principle are within the scope of protection of the present invention.

[0021] A method for preparing a WC particle reinforced nickel-based alloy gradient composite coating on a non-magnetic steel surface by laser cladding, such as Fig.14 As shown, the specific steps are as follows: Powder mixing: Inconel 625 alloy powder and WC powder of corresponding molar ratio are weighed and mixed and put into a ball mill. The mixed powder is stirred at 300 rpm for 24 hours using a ball mill to mix them thoroughly.

[0022] Powder drying: Put the mixed powder into a beaker and place it in a drying oven at 150°C for 12 hours under vacuum.

[0023] Substrate pretreatment: The substrate pretreatment is to remove the oxide layer on the substrate surface by mechanical grinding, then polish it flat with sandpaper, and then clean it with ethanol solution to remove surface oil stains.

[0024] Laser cladding: The laser cladding experiment used the laser cladding equipment of Nanjing Zhongke Yuchen Laser Technology Co., Ltd., model RC-HSLC-6000. The laser is a fiber laser of Raycus, model RFL-C6000X, with a rated output power of 6 kW and a central wavelength of 1080±5 nm. The position of the laser cladding head was adjusted using a Siemens CNC machine tool. The laser cladding powder nozzle RC52 used a double-barrel powder feeder to mix four powders and then feed them into the molten pool. Both the powder feeding gas and the protective gas were argon. The laser cladding process parameters are different according to the level: the laser power is 2400W, 2600W, and 2900W respectively; the scanning rates are 750mm / min, 650mm / min, and 780mm / min respectively; the powder feeding rates are 21.6g / min, 23.8g / min, and 28.4g / min; the overlap rate is 45%.

[0025] Phase composition and microstructure: The cladding layer samples of the required size were cut by wire cutting machine, and the cross section perpendicular to the cladding direction was selected for inlay. After grinding and polishing, the samples were etched with aqua regia solution prepared according to HCl:HNO3=3:1. The microstructure and elemental composition of the coating were analyzed by Olympus BX53M optical microscope, Guoyi Quantum SEM3100 scanning electron microscope and Oxford Xplore15 energy spectrometer; the phase composition of the coating was detected by Rigaku UltimaIV X-ray diffractometer of Japan.

[0026] Microhardness: The HVS-1000 Vickers hardness tester was used to test the microhardness of the coating. The applied load was 1 kg and the loading time was 10 s. The cross-sectional microhardness test scheme was to start from the point near the surface of the cladding layer, and then to make 3 points at the same distance from the surface every 200 μm to take the average value. The longitudinal test point interval was 200 μm. Friction and wear: A Bruker UMT TriboLab reciprocating friction and wear tester was used for dry sliding friction experiments, with a load of 50 N, a friction and wear time of 12 min, a friction and wear stroke of 20 mm, a reciprocating frequency of 1 Hz, and a 6.5 mm silicon nitride ball as the counter-wear pair; an Olympus DSX1000 ultra-depth microscope was used to detect the three-dimensional morphology and surface roughness of the coating surface; Electrochemical corrosion: According to GB / T 10125-2012 standard, the copper accelerated acetic acid salt spray corrosion test (CASS) was carried out using a TLE-90C salt spray test machine (see Table 1). The specific experimental parameters are shown in Table 1. The electrochemical corrosion experiment was carried out using a CHI760E electrochemical workstation produced by Shanghai Chenhua. The specific experimental parameters are shown in Table 1.

[0027] Table 1 Corrosion test parameters Impact toughness: The coating was made into impact specimens, and the impact toughness of the impact specimens was tested using a Charpy pendulum impact tester. The test temperature was room temperature. Three specimens were prepared for each coating content, and the average value was taken to compare the impact toughness of the coating. The fracture morphology was observed using SEM.

[0028] Figure 1 a shows the overall SEM morphology of the gradient composite coating, in which no obvious defects such as cracks and pores are observed. At the same time, the boundaries between the substrate and the bottom layer, and between the bottom layer and the middle layer can be clearly observed, while the boundary between the middle layer and the top layer is not obvious. The main reason is that the composition of the cladding powder in the middle layer and the top layer is not much different, and their physical properties are slightly different, so the macroscopic morphology formed is relatively similar. Figure 1 b shows an enlarged view of the bonding area between the bottom layer and the substrate. A "bright white band" can be observed, indicating that the bottom layer and the substrate are metallurgically bonded. This "bright white band" is caused by the growth of the micro-melting zone near the substrate at the bottom of the first sub-layer in the form of planar crystals. The first sub-layer has a dense structure without obvious defects such as pores and cracks; cellular crystals and columnar crystals are the main organizational forms in the bonding area between the bottom layer and the substrate. Figure 1 c is an enlarged view of the bottom layer and the middle layer combination area. There is a clear dividing line between the bottom layer and the middle layer. A large number of white phases are distributed on the dividing line. This is because the molten WC decomposes during the cladding process and reacts with the Inconel 625 matrix to generate a white carbide phase. The particle carbide phase is easy to settle at the bottom of the molten pool due to its high density and the strong stirring of the molten pool, that is, the dividing line. Columnar crystals are the main organizational form of the bottom layer and the middle layer combination area. Figure 1 In c, the cross-layer epitaxial growth characteristics of columnar crystals can also be seen, and the growth direction is toward the center of the molten pool. In addition, no holes or cracks were found in the entire coating, which shows that laser cladding can effectively improve the wettability and bonding between the ceramic reinforcement phase and the matrix material and the transition distribution of the reinforcement phase between the coatings by melting the external ceramic particles and reacting the endogenous hard phase, thereby avoiding the ceramic phase as the root cause of cracks.

[0029] Figure 2 The metallographic microstructures at different positions of the gradient coating. Figure 2a is the morphology of the bonding area between the substrate and the bottom layer (first sublayer). There is an obvious heat-affected zone in the bonding area. The microstructure at the interface is planar crystals, cellular crystals, and columnar crystals from the substrate to the coating. Figure 2 b is the morphology of the bottom layer (first sublayer), from which it can be seen that the bottom layer structure is mainly composed of short, thick and sparse columnar crystals. Figure 2 c is the morphology of the middle layer (second sublayer), from which it can be seen that the middle layer structure is mainly composed of slender and dense columnar crystals accompanied by undissolved WC particles. Figure 2 d is the morphology of the top layer (third sublayer). It can be seen that the top layer structure is mainly composed of short, dense columnar crystals and irregular equiaxed crystals, and the undissolved WC particles are larger and more numerous.

[0030] Figure 3 The SEM local microstructures of different areas of the gradient coating are shown. Figure 3 a shows the scanning electron microscopic morphology of the interface between the first gradient sublayer and the second gradient sublayer. It can be seen from the figure that the content of the WC phase precipitated at the interface and the carbide phase generated by the reaction is relatively high; Figure 3 b shows the scanning electron microscopic morphology of the second gradient sublayer. It can be seen that the microstructure is mainly columnar dendrites, with carbide phases distributed between the dendrites; Figure 3 c shows the scanning electron microscopic morphology of the bottom of the first gradient sublayer, from which it can be seen that the microstructure is mainly cellular crystals; Figure 3 Figure d shows the scanning electron microscopy morphology of the top of the third gradient sublayer. It can be seen that the microstructure is mainly equiaxed crystals, and there are more carbide phases distributed at the grain boundaries.

[0031] right Figure 3 The EDS element composition was detected at each point in the gradient coating shown in the figure. The mass fraction of some elements at each point is shown in Figure 4 As shown. Figure 4 The element composition test results show that in the interdendritic region ID ( Figure 3 Points 2, 4, 6, and 8) are distributed with a large amount of C, Nb, Mo, Cr and other elements. The dendrite region DR ( Figure 3Points 1, 3, 5, and 7) are distributed with a large number of elements such as Ni and Fe. Due to the eutectic reaction during the solidification of Inconel 625, on the one hand, Fe solute atoms are dissolved in the Ni solvent lattice to form γ-Ni austenite dendrites, and on the other hand, Nb and Mo elements will segregate into the interdendritic region to form Laves phase. On the other hand, after WC is dissolved and decarburized, the carbide phase generated by the reaction of carbon with the alloying elements in the Inconel 625 alloy is also distributed in large quantities in the interdendritic region. The tendency to form carbides can be evaluated by comparing the Gibbs free energy change ΔG values ​​of different metal elements to form carbides. The more negative the ΔG value, the stronger the tendency to form carbides, that is, the easier it is for the reaction to proceed spontaneously. Carbon and the alloying elements in the Inconel 625 alloy are ranked according to the difficulty of forming carbides (from easy to difficult): Nb>Mo>Cr>Fe>Ni. Therefore, the interdendritic region ID ( Figure 3 Points 2, 4, 6, 8) have high contents of C, Nb, Mo, and Cr, and the dendrite axis DR ( Figure 3 Points 1, 3, 5, 7) have high content of Ni and Fe elements.

[0032] Combination Figure 5The phase spectrum of the gradient coating shown in the figure is analyzed. The first sublayer is composed of eutectic γ+Laves phase, and the main phase is FCC structure γ-Ni solid solution. Due to the low content of Laves phase, no corresponding diffraction peak is found in the XRD spectrum, and the XRD spectrum shows a three-strong peak distribution. During the laser cladding process of the second and third sublayers, with the addition of WC, the C element generated by WC decarburization undergoes a synthesis reaction. On the one hand, it diffuses into the interdendritic region ID and reacts with Nb, Mo and other elements in Inconel 625 to form carbide phases such as MC and M2C; on the other hand, it diffuses into the dendrite region DR and reacts with Fe, Cr and other elements in Inconel 625 to form carbide phases such as M6C and M23C6, which are attached to the main phase γ-Ni solid solution. The structure of the second and third sublayers gradually changes from a single-phase FCC structure to a complex phase structure of FCC (γ-Ni matrix phase) + intermetallic compounds (carbide phase and Laves phase) + undissolved WC. The carbide phase mainly includes WC, W2C, NbC, Fe3W3C, and Cr23C6, which have precipitation strengthening and dispersion strengthening effects, increasing the strength, hardness and wear resistance of the material. Due to the large number and types of carbide phases, the number of diffraction peaks in the diffraction patterns of the second and third sublayers is large and the intensity is large, but because of the low content of the Laves phase, no corresponding diffraction peaks are observed. In addition, the main diffraction peaks of the second and third sublayers are offset relative to the first sublayer, indicating that complex phase changes have occurred in the gradient composite coating. This is because the WC particles are decarburized under the repeated action of laser to form a large amount of W2C and C. A part of the enriched C atoms react with metal atoms at high temperature to form a variety of carbides, and the other part is dissolved in the matrix phase, resulting in lattice distortion, increasing the lattice constant and the crystal plane spacing, causing the diffraction peak to shift to a smaller angle.

[0033] Compared with the single coating (30wt% WC), the diffraction spectrum of the third sublayer (30wt% WC) of the gradient coating has the same phase type, but some new diffraction peaks appear, and some of the original diffraction peaks are strengthened. The reason is that due to the reciprocating processing of the laser, the gradient coating has a significant preheating effect, the atomic diffusion movement is enhanced, the WC content at the top of the coating is increased compared to the single-layer 30wt% WC coating, and the carbide phase in the coating increases. In addition, the main diffraction peak of the third sublayer shifts to the left relative to the single-layer coating. This is because the laser remelting effect causes more C atoms in the third sublayer to be dissolved in the matrix phase, resulting in more serious lattice distortion.

[0034] In summary, as the amount of WC added increases, the content of γ-Ni solid solution gradually decreases, the content of undissolved WC increases, and the content and type of carbide phases gradually increase. In summary, the method and process cost of a rare earth oxide dispersion-strengthened FeCoNiCrMn high-entropy alloy coating provided by the present invention are low, and the prepared high-entropy alloy composite coating has good comprehensive mechanical properties, which effectively solves the application of high-entropy alloys in the field of mechanical manufacturing.

[0035] Figure 6 This is an EDS line scan image around the undissolved WC powder particles. It can be seen from the figure that in addition to the WC particle position, the W and C contents in other line scan areas also surge, proving that there are secondary phases generated by the reaction of W or C with other elements at this position. The locations where Mo and Nb content is enriched are Laves phases or carbide phases such as MC and M2C in the interdendritic region; while the locations where Fe and Cr content is enriched are carbide phases such as M6C and M23C6 in the dendrite axis region. The locations with higher Ni content are mainly matrix phases. The third sublayer (30% WC) has more violent and frequent fluctuations in element content than the second sublayer (15% WC), mainly because the third sublayer contains more carbide phases.

[0036] Figure 7 The microhardness changes of the gradient composite coating shown in the figure. The uneven content and distribution of WC undissolved particles and carbide phases in each cladding layer cause the hardness value of the gradient coating to fluctuate greatly. Since the hardness value of WC particles is high and the hardness value of the Ni-based bonding phase in the coating is low, when the indenter of the hardness tester is pressed on the WC particles, its hardness value will increase, and when the indenter of the hardness tester is pressed on the bonding phase, its hardness value will decrease, so it shows a certain fluctuation. The average microhardness of the third gradient sublayer is 529.88HV1, the average microhardness of the second gradient sublayer is 492.03HV1, and the average microhardness of the first gradient sublayer is 447.48HV1. The average microhardness of the third gradient sublayer is slightly different from that of the second gradient sublayer. The microhardness of the third gradient sublayer is 1.78 times that of the substrate and 1.15 times that of the Inconel625+30%WC single composite coating. This is mainly because the gradient change of the composition of the cladding material in the gradient coating weakens the difference in mechanical and physical properties between the cladding material and the substrate, improving the coating quality. At the same time, as the WC content in the gradient coating increases, the secondary hard phase in the coating increases significantly, and the fine grain strengthening and dispersion strengthening effects increase, which improves the coating hardness. Due to the preheating effect of the first two layers, the molten pool temperature of the third sublayer is high and the life is long, resulting in sufficient diffusion of the C element produced by the decomposition of WC. On the one hand, it undergoes carburization reaction with other elements to generate more hard carbide phases, and on the other hand, it dissolves in the matrix phase to produce solid solution strengthening, resulting in the hardness of the third sublayer being higher than that of the 30%WC single composite coating. Due to the transitional change of the composition of the gradient coating, the hardness distribution curve also shows a step effect.

[0037] The cladding process of gradient coating gradually adds WC strengthening phase from the inside to the outside, making the coating structure hard on the outside and tough on the inside. That is, the coating surface has higher hardness and wear resistance, while the core has higher plasticity and toughness. This structure is conducive to improving the service life of the coating and adapting to harsh service conditions.

[0038] Figure 8The friction coefficient diagrams of substrate, Inconel 625 coating, 30% WC coating and gradient coating are shown. The friction and wear process is mainly divided into three stages: running-in wear, stable wear and severe wear. The friction coefficients of all coatings fluctuate significantly in the running-in wear stage (the first 100s). This is because the contact surface between the substrate / coating and the friction pair will continuously generate wear debris as the wear progresses, increasing the roughness of the coating, which in turn causes the initial friction stage to be very unstable, so the friction coefficient curve fluctuates violently, but generally shows an upward trend. As the running-in stage progresses, the friction surfaces gradually adapt to each other. After reaching a certain equilibrium position, the friction coefficient gradually stabilizes and enters the stable wear stage after 100s. In the stable wear stage, the friction coefficients of the substrate, Inconel 625 coating, 30% WC coating and gradient coating fluctuate around 0.52, 0.38, 0.33 and 0.30 respectively. Among them, the substrate and Inconel 625 coating have low hardness and poor wear resistance, so the fluctuation range of the friction coefficient is relatively large. The curves of both coatings even show a downward trend in this stage because abrasive wear occurs in this stage. After the abrasive enters the friction area, it will reduce friction, making the wear surface gradually smooth and reducing the friction coefficient. As the friction and wear proceed, a large number of abrasive particles will be squeezed to the edge of the wear mark by the friction pair to become adhesives, causing the surface morphology of the substrate / coating (from furrows to adhesives) and the wear mechanism (from abrasive wear to adhesive wear) to change. Therefore, it can be observed that the friction coefficient increases significantly after the friction and wear proceeds to 550s, indicating that it has entered the severe wear stage. In contrast, the fluctuation range of the friction coefficient of the 30% WC composite coating and the gradient composite coating in the stable wear stage is relatively stable. Among them, the 30% WC coating enters the severe wear stage after the friction and wear proceeds to 650s, while the friction coefficient curve of the gradient coating does not show an obvious upward trend in the final stage, indicating that its friction and wear has not yet entered the severe wear stage. By comparing the friction coefficients of the substrate and the coating, it can be seen that the average friction coefficient of the gradient coating is smaller than that of the coating with 30% WC added, and is much smaller than the friction coefficients of the substrate and Inconel 625 coating, indicating that the friction reduction properties of the samples are ranked from best to worst as follows: gradient coating > 30% WC coating > Inconel 625 coating > substrate.

[0039] Fig. 9 The figure shows the wear loss of the substrate, the coating with 30% WC and the gradient coating. It can be seen from the figure that the gradient coating has the smallest wear loss of 0.6 mg and the wear rate is 0.4167×10 -3 mg·m -1 ·N -1 (The wear loss of the substrate is 9.8 mg, and the wear rate is 6.8056×10 -3 mg·m -1 ·N -1; The wear loss of Inconel 625 single-layer cladding layer is 4.0 mg, and the wear rate is 2.7778×10 -3 mg·m -1 ·N -1 ; The wear loss of 30wt% WC single-layer cladding layer is 1.4mg, and the wear rate is 0.9722×10 -3 mg·m -1 ·N -1 ), the wear resistance of the gradient coating is improved by 94% compared with the substrate and 57% compared with the 30% WC coating. It can be seen from the wear volume that the wear resistance of the gradient coating has been significantly improved compared with the 30% WC coating. This is mainly because the gradient coating realizes the composition transition between the layers, reducing the thermal expansion mismatch and interface stress concentration caused by the large difference in the physical properties of the matrix phase and the ceramic phase. The bonding phase supports and fixes the hard phase during the wear process, preventing the hard phase from shifting and falling off when subjected to shear force. The smaller the size of the hard phase, the stronger the pinning ability of the bonding phase. The hard carbide phase of the 30% WC coating is large in size. When the strength of the hard phase combined with the bonding phase is not enough, it is easy to move under the action of external force, and eventually fall off from the bonding phase, exacerbating the degree of wear of the coating. The hard phase of the gradient coating is smaller in size, and the strength of the bonding phase is increased, and the wear resistance is better.

[0040] Fig.10 a shows the wear morphology of the substrate. It can be observed that the surface of the non-magnetic steel substrate is worn with multiple parallel furrows of varying depths and large widths, and a small amount of adhesive debris appears near the furrows, indicating that the substrate is severely worn. The appearance of furrows after material wear shows typical micro-cutting abrasive wear characteristics; the adhesive near the grooves shows smearing adhesive wear characteristics. Combining the above analysis, it can be seen that abrasive wear and adhesive wear are the main wear mechanisms of the substrate. The main reason is that the hardness of the matrix phase is relatively low, and dislocation sliding occurs under the combined action of friction and applied load, inducing plastic deformation, shearing off to become wear debris, and material transfer and smearing occur, thereby producing adhesive wear and forming adhesives. In addition, the hard phase in the matrix will fall off during the wear process, enter the friction pair to form abrasive particles, resulting in abrasive wear and the formation of furrows.

[0041] Fig.10b shows the wear morphology of Inconel625 coating. During the friction process, the contact point of Inconel625 coating first undergoes plastic deformation and is in a plastic flow state. In addition, the contact point on the coating surface generates instantaneous high temperature due to friction and deformation. The high temperature causes the local metal to melt and weld, resulting in softening and adhesion. Under the action of friction, the adhesion point is sheared, detached, and slides between the friction surfaces. The formation and shearing of this adhesion contact node occur alternately during the sliding friction process. The friction force of Inconel625 coating is divided into two stages during the friction process. The first stage is mainly manifested by shear force. Under the action of shear force, the softer γ-Ni phase at the contact point of Inconel625 coating undergoes plastic deformation and falls off. After re-welding under the action of flash temperature, it adheres to the friction pair and the coating as wear debris; the second stage is mainly manifested by furrow force. Under the action of furrow force, nickel-based matrix phase wear debris falls off from the friction surface, and part of it adheres to the friction pair, causing abrasive wear on the coating surface, resulting in furrows of varying depths on the coating surface. Fig.12 As shown in (b), the Inconel625 coating is distributed with a large amount of adhered grinding chips and other adhesives, accompanied by slender and undulating furrows. Therefore, the wear mechanism of the Inconel625 coating is mainly smear adhesive wear, supplemented by micro-cutting abrasive wear.

[0042] Fig.10 c shows the wear morphology of 30% WC coating. The main feature of WC reinforced Inconel625 coating is the heterogeneous structure with many hard particles distributed on the soft plastic matrix. During the friction and wear process, the hard carbide phase protruding from the friction surface directly bears the load, while the soft nickel-based matrix phase plays the role of supporting the hard phase. As the main contact bearing phase, the hard carbide phase significantly affects the wear resistance of the coating. First, the protruding carbide particles can play a supporting role, forming a "shadow effect" to protect the matrix metal; second, the dispersed undissolved WC particles and the precipitated carbide phase can block the continuous "ploughing" of the abrasive particles on the wear surface, which has a wear-resistant effect; third, the fine hard phase plays the role of "fine ball" on the friction contact surface, converting the sliding friction part into rolling friction, thereby reducing the friction coefficient and the degree of wear. When the load reaches a certain level, the pressure on the coating surface increases, causing the hard phase particles to sink into the soft matrix, so that more hard phase particles bear the positive load and achieve the purpose of uniform load distribution. By Fig.10As can be seen from Figure c, the worn surface shows long and thin scratches. This is because the friction pair has a high hardness. Under the action of the normal load, the friction pair presses the hard phase particles protruding from the coating surface into the soft matrix. Under the action of sliding friction, the surface is sheared, plowed and cut by the abrasive, thereby removing the nickel matrix material that is softer than the reinforcing phase on the surface of the coating, resulting in long and thin scratch-like shallow wear marks. A small amount of removed nickel matrix wear debris adheres to the coating surface, so the wear mechanism is manifested as abrasion adhesive wear and smear adhesive wear. In addition to the dominant adhesive wear mechanism, there is also a certain amount of fatigue wear on the coating surface, which is manifested as pitting pits and flaking layers on the surface. The pitting pits and flaking layers are typical manifestations of pitting and flaking fatigue wear, respectively. The reason for pitting fatigue wear is that under the action of high contact pressure stress, after multiple cycles, small pieces of surface metal fall off in local areas of the friction surface, forming pockmarked pits; the reason for spalling fatigue wear is that the cyclic stress formed in the contact area exceeds the fatigue strength of the coating, causing cracks on the coating surface and gradually expanding, and finally causing the flaky surface metal in the area surrounded by the cracks to break and peel off.

[0043] Fig.10 Figure d shows the wear morphology of the gradient coating. There are a large number of pits and a small amount of flaky peeling layers on the surface of the gradient coating, accompanied by fine and slight scratches, indicating that the dominant pitting fatigue wear and abrasion adhesion wear mechanisms, as well as the secondary peeling fatigue wear mechanism, occurred. The WC particles and the hard phase produced during the laser coating process exist in the coating in a slightly raised form, forming a "frame" for the matrix phase, playing a role of protruding load, slowing down the friction between the ceramic ball and the coating surface. The larger volume of hard phase particles is easily pressed into the soft matrix phase by the friction pair, while the smaller volume of hard phase will become loose during the friction and wear process, and detach from the friction surface under the action of friction. Part of the peeled hard small particles adhere to the friction pair, causing fine scratches on the coating surface. In addition, compared with the coating with 30% WC added, the number of hard carbide particles in the gradient coating increases, which increases the probability of pitting fatigue wear; the increase of unmelted WC particles and hard phases in the gradient coating improves the friction reduction and wear resistance of the coating, thereby reducing the amount of flaking layer produced.

[0044] Fig.11 The figure shows the comparison of the three-dimensional morphology parameters of the coating wear scar. Fig.12 and Fig.13The overall three-dimensional morphology and local three-dimensional morphology of the coating wear scar. Compared with the substrate and uniform composition coating, the roughness and maximum valley depth of the gradient coating are significantly reduced, indicating that the wear resistance of the gradient coating is improved. The reason for the excellent wear resistance of the gradient coating is that the hard phase diffused into the substrate is difficult to peel off, which makes the content of the hard phase in the gradient coating higher and the number larger. At the same time, WC particles inhibit grain growth, promote heterogeneous nucleation, and refine the microstructure. Therefore, the fine grain strengthening produced by WC particles in the gradient composite coating and the precipitation strengthening and dispersion strengthening produced by the hard phase are the main factors for improving the wear resistance of the gradient coating. In addition, the lattice distortion of the FCC matrix phase will also increase with the addition of WC. The wear resistance of the gradient composite coating is improved by the solid solution strengthened FCC matrix phase and the dendritic precipitation of intermetallic compounds and eutectic mixtures.

[0045] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the schemes disclosed herein. The present invention is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed in this disclosure. The description and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the claims.

Claims

1. A WC particle reinforced nickel-based alloy gradient composite coating laser clad on a non-magnetic steel surface, characterized in that: The raw materials of the composite coating are Inconel 625 alloy powder and tungsten carbide WC particles. The gradient composite coating is divided into three layers, and the thickness of each layer is 0.9-1.1 mm.

2. The WC particle reinforced nickel-based alloy gradient composite coating laser cladding on the surface of non-magnetic steel according to claim 1 is characterized in that: The mass percentages of the Inconel 625 alloy powder and tungsten carbide WC particles in different gradients are: first gradient sublayer: 100% Inconel 625 - 0% tungsten carbide WC, second gradient sublayer: 85% Inconel 625 - 15% tungsten carbide WC, third gradient sublayer: 70% Inconel 625 - 30% tungsten carbide WC, wherein the particle size of the Inconel 625 alloy powder is 53-150 μm; the particle size of the tungsten carbide WC particles is 30-80 μm.

3. A method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface as claimed in claim 1, characterized in that: include: Step 1, ball-milling and mixing Inconel 625 alloy powder and WC particles to obtain mixed powder; Step 2: Put the mixed powder into a beaker and place it in a drying oven for drying to obtain dry powder; Step 3, pre-treating the substrate surface; Step 4: The dry powder is clad onto the treated substrate through a synchronous powder feeding laser cladding device to obtain a WC particle reinforced Inconel 625 composite coating.

4. The method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface according to claim 3, characterized in that: In step 1, the ball mill stirs the mixed powder at a rotation speed of 200-500 rpm for 12-24 hours, and the mass percentage of the ball-milled mixed ceramic balls and the alloy powder is 1:

1.

5. The method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface according to claim 3, characterized in that: In step 1, the mass percentage of the ball-milled mixture of the Inconel 625 alloy powder and the WC particles is divided into three gradients: the first gradient sublayer: 100% Inconel 625 - 0% WC, the second gradient sublayer: 85% Inconel625 - 15% WC, the third gradient sublayer: 70% Inconel 625 - 30% WC, wherein the particle size of the Inconel 625 alloy powder is 53-150 μm; the particle size of the WC particles is 30-80 μm.

6. The method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface according to claim 3, characterized in that: In step 2, the operating temperature of the drying oven is 120-150° C., and the time is 8-12 hours.

7. The method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface according to claim 5, characterized in that: In step 3, the substrate is pretreated by removing the oxide layer on the surface of the substrate by mechanical grinding, then polishing it flat with sandpaper, and then cleaning it with ethanol solution to remove surface oil stains.

8. The method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface according to claim 3, characterized in that: In step 4, the laser cladding process parameters are different according to the levels: the laser powers are 2400W, 2600W, and 2900W respectively; the scanning rates are 750mm / min, 650mm / min, and 780mm / min respectively; the powder feeding rates are 21.6g / min, 23.8g / min, and 28.4g / min; and the overlap rates are all 45%.

9. The method for preparing a WC particle reinforced nickel-based alloy gradient composite coating by laser cladding on a non-magnetic steel surface according to claim 3, characterized in that: In step 4, the gradient composite coating is divided into three layers, and the thickness of each layer is 0.9-1.1 mm.

Citation Information

Cited By

  • Method and system for predicting wear resistance of nickel-based composite coating based on machine learning

    CN121460031A

  • Laser cladding preparation method for reducing defects of nickel alloy doped WC cladding layer

    CN122214853A

  • Laser cladding nickel-based wear-resistant coating compositely reinforced by micro-nano hard ceramic phase as well as preparation method and application of laser cladding nickel-based wear-resistant coating

    CN122252622A